Dampak Poligami terhadap Perempuan dan Anak dalam Keluarga - Dzakiyatul Qowiy Bathin; Rizky Hilmansyah; Muhamad Hapipi Roif; Humaeroh Humaeroh (Lembaga Pengabdian Masyarakat Universitas Ichsan Gorontalo, 2026)
Polygamy remains a controversial issue in Indonesia, involving legal, religious, and social dimensions. This study aims to analyze the social, psychological, and economic impacts of polygamy on wives and children. Using a qualitative library research approach, the study examines primary sources, including Law Number 1 of 1974 concerning Marriage and the Compilation of Islamic Law, as well as relevant scientific literature and journal articles. The findings indicate that although Indonesian law permits polygamy under strict conditions, such as the wife's consent and the husband's ability to act fairly, these requirements are often difficult to fulfill in practice. Psychologically, wives frequently experience jealousy, emotional stress, depression, and feelings of injustice. Economically, polygamy may lead to the division of family resources, reducing the welfare of wives and children. Children may also experience emotional difficulties due to limited parental attention, conflicts among siblings, and social stigma. These impacts can affect family harmony and child development. Therefore, stronger legal supervision and public education are needed to ensure the protection of women's and children's rights and to minimize the negative consequences of irresponsible polygamous practices.